META-ANALYSIS OF THE APPLICATION OF STEM APPROACH BASED ON HOTS IN PHYSICS SUBJECT ON CRITICAL THINKING SKILLS OF STUDENTS - Aprilia, Putri; Amelia, Mira; Panggabean, Cristina (Universitas Negeri Medan, 2024)
Various skills that must be mastered by students to be able to prepare themselves to match the human resources of developed countries are today's challenges. One of these skills is critical thinking. The application of the STEM approach is a new era to meet the learning objectives in the 21st century. And by applying the HOTS-based STEM approach will improve students' critical thinking skills. The research in this article uses the meta-analysis method by finding the effect size calculation value of each journal analyzed. Thus, it is found that the learning model that has a major effect on the application of the HOTS-based STEM approach is the experimental learning model, with the material of Electricity and Magnetism and with the help of simulation media at the XII grade high school level.Keywords: STEM Approach, HOTS, Critical Thinking